2015
DOI: 10.5604/20815735.1174229
|View full text |Cite
|
Sign up to set email alerts
|

MMA fighters’ technical-tactical preparation – fight analysis: a case study

Abstract: Introduction. An MMA fight gives the participating athletes an opportunity to show a wide range of tactical and technical skills from a variety of martial arts. To be successful in it, one must impose his own fighting style on the opponent and confirm its effectiveness. Materials and methods. The research material consisted of a hundred and eighty-seven technical attacks performed during a 13-minute fight of two MMA fighters (referred to in the paper as Athlete #1 and Athlete #2) belonging to the elite of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…In the fight outcomes by KO, head punches and kicks were, respectively, the predominant skills. This is in line with another MMA study, which showed that one-fifth of all wins by knockout before the end of the regular time results were through head punches [34]. In addition, in the fight outcomes by TKO, the ground and pound was the most used skill, which is in line with a study in which in ground fighting, fighters using the ground and pound, which is associated with a dominant position on the ground, had a clear tactical and technical advantage over their opponent [34].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the fight outcomes by KO, head punches and kicks were, respectively, the predominant skills. This is in line with another MMA study, which showed that one-fifth of all wins by knockout before the end of the regular time results were through head punches [34]. In addition, in the fight outcomes by TKO, the ground and pound was the most used skill, which is in line with a study in which in ground fighting, fighters using the ground and pound, which is associated with a dominant position on the ground, had a clear tactical and technical advantage over their opponent [34].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, in the present analysis, the majority of the fights (68.8%) ended before 5 min (300 s) by submission, TKO and KO, respectively. In fact, it is known that in MMA, one-fifth of all victories through knockout before the end of the regular time occur in the first minute from the beginning of a round [ 34 ]. In contrast, in regard to the frequency of judo dynamics in the time function, the lowest offensive activity was observed in the first minute of the fight (i.e., 0.17 with the lowest effectiveness 0.03) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…(Miarka et al 2015) n = 2,097 male professional bouts Effort time ( Female participants spend longer in competition engaged in low intensity standing movements than male participants, less time in low intensity standing and grounded movements than males. (Adam et al 2015) n = 1 professional, regional bout between two male MMA competitors ( Lactate (mmol•L -1 )= 9.25 ± 2.96; W:R = 1:1.01; bout winners takedowns = 3 ± 1 (attempted 4 ± 2), bout losers takedowns = 0 (attempted 2 ± 2)…”
Section: Predictors Of Performancementioning
confidence: 99%
“…In addition to the time characteristics, the analysis of technical and tactical actions of athletes attracts the attention of researchers [9]. Thus, a technical-tactical preparation-fight analysis for athletes belonging to the elite of the Polish MMA organization was conducted and the structure and composition of athletes ' actions in combat and their effectiveness were considered [10]. It is worth noting that the work considers the top athletes who are in the leaders of the UFC rating.…”
Section: Introductionmentioning
confidence: 99%